2008
DOI: 10.1080/03014460802337067
|View full text |Cite
|
Sign up to set email alerts
|

Do women with polycystic ovary syndrome (PCOS) report differences in sex-typed behavior as children and adolescents?: Results of a pilot study

Abstract: Results of this pilot study provide evidence of PCOS women self-reporting discrete psychosocial developmental patterns compared to non-PCOS women. These differences in retrospective self-reported accounts may be factual or biased by current psychosocial differences, such as depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…In the study by Trent et al [6], girls with PCOS experienced lower quality of life and those who had higher self-perceived severity of illness scored lower on a general health perception scale. BMI was a primary mediator in the quality of life reduction [24]. In contradiction, our study did not demonstrate any relationship between hirsutism score or BMI z-score with SCI parts, however BMI in our patients was much lower than in the adolescents evaluated by Trent et al [26] (26.9 ± 6.3 vs. 31.7 ± 8.4 kg/m 2 ).…”
Section: Prace Oryginalnecontrasting
confidence: 55%
See 1 more Smart Citation
“…In the study by Trent et al [6], girls with PCOS experienced lower quality of life and those who had higher self-perceived severity of illness scored lower on a general health perception scale. BMI was a primary mediator in the quality of life reduction [24]. In contradiction, our study did not demonstrate any relationship between hirsutism score or BMI z-score with SCI parts, however BMI in our patients was much lower than in the adolescents evaluated by Trent et al [26] (26.9 ± 6.3 vs. 31.7 ± 8.4 kg/m 2 ).…”
Section: Prace Oryginalnecontrasting
confidence: 55%
“…The differences could also be attributed to the younger age because some gender roles are acquired over time ("I as a wife", "I as a mother"). In the pilot study by Manlove et al [24], women who suffered from PCOS in adulthood also did not demonstrate different scores on Bem's androgyny scale during adolescence compared to the control group and had similar sex-typical behaviours. However, they did have lower self-esteem, perceiving themselves to be "different" and had less social interaction with their peers.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Lower body-image has been found to be associated with sexual avoidance (35). There is evidence that sex typed behavior and sexual orientations are related to hormonal levels as one study measured sex-typed behavior by internet survey as well as self-reported PCOS diagnosis (36). The results indicated that PCOS women reported significantly less typical feminine behavior as a child (e.g., experimenting with make-up).…”
Section: Discussionmentioning
confidence: 99%
“…Diamond did not discuss whether a high amount of prenatal testosterone could account for a woman having a stronger sex drive. However, research on polycystic ovary syndrome, characterised by higher than normal testosterone levels in women, suggests higher reports of bisexuality and changing sexual orientation than the control group of women (Manlove et al 2008). …”
Section: Discussionmentioning
confidence: 99%